2016
DOI: 10.1039/c5nj03252k
|View full text |Cite
|
Sign up to set email alerts
|

Facilely synthesized N-doped carbon quantum dots with high fluorescent yield for sensing Fe3+

Abstract: Schematic illustration of the preparation process for the NCQDs and their application for Fe3+ ions detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 50 publications
1
58
0
Order By: Relevance
“…Similar to other CQDs reported in literature, [41][42][43] the asprepared CQDs and M-CQDs in aqueous solution exhibited strong luminescence. Figures 6A, S2, and S3 show the UVvis absorption, PL spectra, and excitation spectrum of the CQDs and M-CQDs in aqueous solution, respectively.…”
Section: Photophysical Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…Similar to other CQDs reported in literature, [41][42][43] the asprepared CQDs and M-CQDs in aqueous solution exhibited strong luminescence. Figures 6A, S2, and S3 show the UVvis absorption, PL spectra, and excitation spectrum of the CQDs and M-CQDs in aqueous solution, respectively.…”
Section: Photophysical Propertiessupporting
confidence: 72%
“…The significantly reduced lifetime indicates the occurrence of dynamic quenching and confirms that the electron transfer between Fe 3+ and CQDs contributes to the fluorescence quenching. 43,49 …”
Section: The Ion Sensing Of Cqdsmentioning
confidence: 99%
“…The former signal corresponds to the π-π * transitions of conjugated systems, and the latter signal corresponds to the n-π * transition of the carbonyl groups. 25,41,42 The inset in Figure Figure 3. FTIR spectrum of the N-CQDs.…”
Section: Resultsmentioning
confidence: 99%
“…Modification of the surface properties could be achieved by doping the CQDs, often with nitrogen. 24,25 For example, it has been demonstrated that N-doping of CQDs increases quantum yield and electron transfer.…”
mentioning
confidence: 99%
See 1 more Smart Citation